Internalizing Fathonah Character in Critical Reasoning: A Case Study of Islamic Values Integration in Science and Social Studies - Supriyadi, Supriyadi; Enik Setiyawati; Tobroni, Tobroni; Moncef Ben Abdeljelil; Asyraf Isyraqi Bin Jamil (Scidac Plus, 2026)
This study aims to analyze the internalization of the fathonah (intellectual excellence) character in strengthening students' critical reasoning through the reconstruction of the discovery learning model within Natural and Social Sciences (IPAS) instruction at Al-Uswah Nature Integrated Islamic Elementary School (SDIT), Pasuruan. Primary education currently faces the challenge of cognitive disruption due to the massive influx of unverified information, necessitating the reinforcement of high-integrity critical reasoning. This research employed a qualitative case study design, with data collected through observation, interviews, and documentation involving fourth-grade teachers and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, conducted simultaneously through data condensation, data display, and conclusion drawing. To ensure data trustworthiness, technical triangulation, prolonged engagement, and peer debriefing were utilized. The research findings reveal that the internalization of prophetic values successfully transformed mechanistic cognitive procedures into transcendental learning experiences through the reconstruction of a five-phase syntax: (1) stimulation as initial tafakkur (reflection); (2) data collection as scientific amanah (trustworthiness); (3) data processing as a manifestation of itqan (precision/excellence); (4) verification as an act of theological tabayyun (validation); and (5) generalization as the formulation of hikmah (wisdom). The synthesis between fathonah values and Vygotsky’s Social Constructivism generates a